Society and Communication in the Global South: Negotiating Identity, Power, and Meaning in Contemporary Social Life - Muhammad Khofidul A (Professorline, 2026)
In contemporary society, communication plays a central role in shaping social relations, identities, and power structures. Beyond formal media systems, everyday communication practices ranging from interpersonal interaction to community-based discourse serve as key sites where social meanings are produced and negotiated. This perspective examines society as a communicative process, with particular attention to Global South contexts characterized by cultural plurality, historical inequality, and uneven access to communication resources. Drawing on insights from communication studies, the article argues that social life is constituted through ongoing negotiations of meaning, authority, and belonging. By foregrounding communication as a social practice, this article highlights its significance for understanding contemporary society beyond media-centric approaches.